Health system and societal barriers for gestational diabetes mellitus (GDM) services - lessons from World Diabetes Foundation supported GDM projects - Nielsen Karoline Kragelund; de Courten Maximilian; Kapur Anil (BMC, 2012)
Abstract Background Maternal mortality and morbidity remains high in many low- and middle-income countries (LMIC). Gestational Diabetes Mellitus (GDM) represents an underestimated and unrecognised impediment to optimal maternal health in LMIC; left untreated - it also has severe consequences for the offspring. A better understanding of the barriers hindering detection and treatment of GDM is needed. Based on experiences from World Diabetes Foundation (WDF) supported GDM projects this paper seeks to investigate societal and health system barriers to such efforts. Methods Questionnaires were filled out by 10 WDF supported GDM project partners implementing projects in eight different LMIC. In addition, interviews were conducted with the project partners. The interviews were analysed using content analysis. Results Barriers to improving maternal health related to GDM nominated by project implementers included lack of trained health care providers - especially female doctors; high staff turnover; lack of standard protocols, consumables and equipment; financing of health services and treatment; lack of or poor referral systems, feedback mechanisms and follow-up systems; distance to health facility; perceptions of female body size and weight gain/loss in relation to pregnancy; practices related to pregnant women's diet; societal negligence of women's health; lack of decision-making power among women regarding their own health; stigmatisation; role of women in society and expectations that the pregnant woman move to her maternal home for delivery. Conclusions A number of barriers within the health system and society exist. Programmes need to consider and address these barriers in order to improve GDM care and thereby maternal health in LMIC.